OPTIMALISASI BRANDING PRODUK DAN STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN VISIBILITAS UMKM BAMBU SILVER - Wayan Sri Jayanti, Ni; W Bandem Wahyu Pratama Niarta , I; Made Pradipta , I; Made Angga Fajar Wedananta, I (Education and Talent Development Center of Indonesia, 2025)
The community service partner is an MSME engaged in the sale of silver jewelry, namely Bambu Silver By Stela Gea. The main problems faced by partners are a) the partners' understanding of product branding is not yet optimal, so that product branding, b) the partners' lack of understanding of structured marketing strategies, c) financial management is not yet optimal. The target of this Community Partnership Program (PKM) is first, increasing the ability of partners with the criteria that 80-100 percent of participants have skills in branding and marketing strategies. The target participants in this PKM are 4 people. The implementation method in the Community Partnership Program (PKM) is divided into several stages, namely; planning, implementation, evaluation and reflection. The results of the community service activities show that (1) there is an increase in the ability of partners in product branding through the development of logo designs with an average of 81.25 in the good category. 2) there is an increase in the ability of partners in marketing through e-commerce with an average of 80 in the good category. 3) an increase in the ability of partners in financial management using financial management applications in Excel with an average of 82.5 in the good category.